Implementation of Lean Manufacturing Methodology to Improve Scheduling Performance for High-Mix Low Volume Production - Chuang-Chun Chiou; Shih-Shun Wang; Huynh Trung Luong (Recent Progress in Science and Technology Vol. 8, 2023)
Fast change trend in customer’s demand determines the type of production. The "high-mix and low volume" production has become the mainstream of production to meet customer’s need. The main problem of high-mix low volume production is significantly increasing the frequency of set up, causing an increase in set-up time for production. For set-up reduction strategies, Shingo proposed a lean manufacturing methodology called Single Minute Exchange of Die (SMED). The SMED methodology makes it possible to reduce setup (changeover) operations time significantly. In this study, a cable processing company is used as a study case. The potential of faster setup can be completely achieved with SMED method. Furthermore, an optimized scheduling reference indicator is presented for the moulding machine that help decision makers to determine the sequencing rule of scheduling by each criterion through the system to improve the performance.